Does hedging enhance firm value in good and bad times. Issue 1 (5th March 2018) - Alam, Nafis; Gupta, Amit
Abstract : Purpose: The purpose of this paper is to examine if the hedging strategy of the firm adds value to the firm, and if so, is the source of the benefit consistent with the hedging theory? Design/methodology/approach: The paper used data from 129 top non-financial Indian companies spanning a period of 2008-2015 and analyzed using the ordinary least squares regression technique. Findings: The study finds that firms engaged in hedging compared to non-hedgers have less volatility in the firm's value. The use of hedging during the financial crisis is found to be value enhancing for the hedgers. The results also found that some firms do not disclose the notional value of derivatives clearly, which highlights the need of clear regulation for derivative declaration in the annual reports. Research limitations/implications: Research implications of this study are to gain an insight into the hedging effectiveness in the highly volatile Indian market as compared to developed countries. High volatility in the exchange rate of Indian rupee further makes it one of the most relevant markets to study the effect of hedging on the firm's value. Practical implications: Mostly hedging is done purely for risk management, and if managers try to time the market by selective hedging, it can bring a negative impact for the firm. Findings show that managers should manage their hedging strategy based on changing the economic environment and not purely on the firms' financial value. Originality/value: To the authors' best knowledge, this is the first study to extract the dollar value of derivative usage of sample firms and analyze its effectiveness in enhancing firm value in the presence of other financial parameters. This will be an advancement of previous studies, which used hedging as a dummy variable only. Most studies on this topic are carried out in developed countries; there is a limited research on developing markets such as India, and past studies have been more generic one like determinants of hedging and overall derivative scenario.